Current education, an innovative change to improve university education through innovation and collaborative work - Velázquez, Jorge (Advances in Social Sciences Research Journal, 2020)
Education must migrate to issues that today's society demands, attending to present and future scenarios in order to provide efficient and effective solutions. The study aims to demonstrate that collaborative work impacts the personal, educational and work relationships of students. The work is supported by quantitative data applied to an enrollment of 70 university students. As an innovation, the strategies that are implemented to enhance the abilities and skills of the students are elucidated. In Amazcala, 45% of respondents say that teachers are not up-to-date, 52% of the sample alludes that educational innovation does not help promote collaborative work, and 83% mentioned that they have never managed innovation in class. In this sense, innovation, collaborative work, communication and the use of technology are factors that have a direct impact in the educational field because through them the student can acquire a full development in his school career and in the workplace, what permeates the path that current education must follow to develop favorable knowledge in students who are about to enter the professional field.